Modelling reconstruction and tool path generation for machining Polyethylene (PE) insert - Chin, Choon Sien; M. Ikhwan, Zaini Ridzwan; Mohd. Farid, Ismail; Solehuddin, Shuib (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.